Means of Persuasive Influence in Discourse: Consideration of Context and the Aesthetics of Rhyme and Parallelism/ وسائل التأثير الحجاجي في الخطاب مراعاة الحال وجماليات السجع والتوازي - Ru'a Faiq Ibrahim; Othman Abdul Halim Jalout Al-Rawi (Ijaz Arabi Journal of Arabic Learning, 2026)
This study aims to analyze the sources of argumentation in Arabic discourse by examining the rhetorical devices that enhance persuasive and affective power, namely rhyme, saj (rhymed prose), and parallelism. The research focuses on revealing the aesthetic and argumentative roles of these devices in constructing a discourse that unites logic with emotion, thereby creating a coherent system of influence and persuasion. Rhyme is considered one of the most prominent rhetorical tools, as it creates a musical rhythm that captures the audience’s attention and reinforces the intended idea. Saj, on the other hand, adds verbal variety, showcasing the speaker’s eloquence and deepening meaning through phonetic contrast. Parallelism achieves syntactic harmony and semantic rhythm, contributing to the coherence and consistency of the discourse and strengthening its persuasive effectiveness. The study concludes that these rhetorical techniques are not merely ornamental; rather, they serve functional purposes in constructing arguments and reinforcing persuasive positions. They exert both psychological and aesthetic effects, making the discourse stronger, clearer, and more appealing to both intellect and emotion.